(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the relationship between PD1 and PDL-1 gen polymorphisms with incidence toxoplasmosis in type 2 diabetes disease (T2DM). Study Design: Case control study Place and Duration of Study: This study was conducted at the Al-Iamamain Al-Kadhumain Teaching Hospital, Baghdad Iraq from 1st December 2018 to 30th April 2019. Methods: One hundred and eighty patients with Type 2 diabetes mellitus (T2DM) aged 31-79 years, attending the diabetes were enrolled. A control group of 163 healthy subjects was also included. The PCR products of the SNPs were sequenced using the Big Dye Terminator method and compared to sequences in GenBank. Results: Extracted DNA were used for molecular study for determination of the (PD-1.5 C/T rs 2227981) and the (PDL-1 Grs1970000) gene polymorphisms by conventional PCR method using specific primer. Sequencing of PCR products revealed three genotypes for the PD-1.5 C/T(CC, CT, TT). Regarding PD-1 showed no significant difference in each CT and CC genotypes between case and control groups while TT genotype showed significant difference between them. As well as related to PDL-1 showed significant difference between case and control while, CC showed non-significant between case and control groups. A allele significantly higher frequency in controls than cases. In contrast, C allele non-significantly higher frequency in cases than controls Conclusion: There is a significant association between the phenotypic polymorphism of the (PD-1.5 C/T gene rs2227981) Toxoplasmosis and type 2 diabetes for the groups in the current study, as it was found that people who carry the genotype TT are more likely to develop type 2 diabetes than people who carry the genotype CC.